SolidWorks surfacing fundamentals - Perez, Matt (InfiniteSkills, 2014)
"In this SolidWorks Surfacing training video, expert author Matt Perez will show you how to use all of the tools available to you throughout the design process. This course can be used to prepare for the CSWP-Advanced Surfacing exam, and is designed for users that already have a fundamental understanding of the SolidWorks software. You will start by setting up your environment and learning the basics of sketching splines, conics, and parabolas. From there, you will follow along with Matt as he teachings you about each tool individually. This video tutorial also includes a chapter to prepare you for the CSWP-Advanced Surfacing Exam, which requires you to know the functionality of the tools in SolidWorks. By the completion of this computer based training video, you will an in-depth understanding of how to use the tools available to you in SolidWorks, and be able to apply this knowledge to the CSWP-Advanced Surfacing exam. Working files are included, allowing you to follow along with the author throughout the lessons."--Resource description page.